Taking Your iPod touch to the Max : Second Edition - Grothaus, Michael (Apress, 2013)
This is the second edition of Taking Your iPod touch to the Max. It has been completely revised and updated with entirely new content, images, and tips. We talk you through the iPod touch’s new operating system, iOS 4.1, and all of its new features including multitasking, HD video recording, creating folders, and, of course, FaceTime—the revolutionary new way for you to communicate with your friends and family. You’ll learn the gesture-based, Multi-Touch vocabulary that allows you to manipulate the iPod and its hundreds of thousands of apps. We’ll show you how to connect to the Internet, browse the Web, touch your music and videos, and find and download apps from the App Store. You’ll discover how to buy and navigate books using Apple’s incredible iBooks app, view slide shows and photos, send e-mail, create notes and calendars, and even stream video from your iPod to your TV.